An Experimental Study on Partial Replacement of River Sand by Manufacture Sand in Self Compacting Concrete - Govindan, Vijayakumar (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Self-compacting concrete (SCC) is a very fluid concrete and a homogeneous mixture that solves most of the problems related to ordinary concrete. Self-Compacting Concrete gets dense and compacted due to its own self-weight. An experimental investigation has been carried out to determine different characters like workability and strength of Self-Compacting Concrete (SCC).Self-Compacted Concrete is generally defined as the â€œConcrete, which does not need Compaction.â€ It means SCC gets compacted without external efforts like vibration, tamping etc. Due to these characteristics, SCC is ideally suited for concreting structures, which have heavily congested reinforcement or difficult access conditions. In this project, M30 grade concrete were made.Â 25%, 50% and 75% percentage of river sand where replaced by M-sand. The compressive strength, split tension test and flexural strength of concrete obtained at the ages of 7 and 28 days.